Analisis Hubungan Bermain Berbasis TIK dengan Perkembangan Kemandirian Anak Usia Dini - Sidiq, Nurul Jamiah; R, Rika Kurnia; Rusliana, Faradila; Manga, Delvhina; Islami, Andi Nur Maharani (NANAEKE: Indonesian Journal of Early Childhood Education, 2025)
Early childhood independence is a crucial aspect of socio-emotional development and decision-making skills. However, the suboptimal level of independence observed in several early childhood education institutions indicates the need for supportive learning strategies, one of which is through play-based activities involving information and communication technology (ICT). This study aims to analyze the relationship between ICT-based play activities and the independence behavior of young children. The research employed a quantitative correlational approach. Data were collected using two instruments: a questionnaire measuring ICT-based play activities and an instrument assessing children’s independence, both completed by teachers as evaluators. Teachers assessed children’s independence based on their observations during ICT-based play sessions. The sample consisted of 23 teachers (35% of the total teacher population) and 95 children aged 4-5 years (10% of the total student population) in Gowa Regency, selected through simple random sampling. Data were analyzed using Pearson’s correlation test with the assistance of SPSS version 24. The results revealed a very strong and significant relationship between ICT-based play activities and children’s independence behavior (r = 0.872; p < 0.0001).